MODEL PEMBANGUNAN INDONESIA DARI PERSPEKTIF PEMBANGUNAN MANUSIA - Randy Pratama Lumenta (Jurnal Administrasi Publik, 2022)
Currently, human development is a priority program carried out by the Indonesian government during the 2019-2024 period. In measuring the extent to which human development has been achieved, in 1990 the United Nations Development Program (UNDP) introduced the Human Development Index (HDI). This study examines and sees the extent of the impact of human development on development that occurs in Indonesia. The method used in this research is a literature study by reviewing the references relevant to this research. The result of this research is the implementation of human development in Indonesia has the characteristics of a short-term productive type of development. Human development planning in Indonesia which has been going on for a long time is starting to pay off. Finally, the human development planning that is prepared is contained in the RPJP for the period 2005-2024 and is revealed in the 5-year RPJM. The quality of human development in 2021 shows positive growth in both human development and the Indonesian economy. This growth was followed by several relatively positive socio-economic changes, but social problems of poverty and inequality still occur. This indicates that the type of human development carried out by the Indonesian government only focuses on growth and socio-economic changes and changes in other aspects that occur are still inconsistent.